Epidemiological trends and disparities in the global burden of bacterial skin diseases among children and adolescents from 1990 to 2021: an analysis based on GBD 2021 - Hongen Guo; Peixin Zheng (BMC Pediatrics)
Abstract Background Bacterial skin diseases (BSDs) represent a substantial public health concern for children and adolescents worldwide. The emergence of community-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) has further complicated treatment, efforts, highlighting the urgent need for targeted policies aimed at prevention and management. Methods This study utilized data from the Global Burden of Disease (GBD) 2021 database, to analyze the global burden of BSDs among individuals aged 0–19 years from 1990 to 2021. Incidence, prevalence, and disability-adjusted life years (DALYs) were the primary indicators assessed. stratified analysis conducted by gender, age, region, and socio-demographic index (SDI). Temporal trends were evaluated using the estimated annual percentage change (EAPC). Date analysis and visualization were performed using the R programming language. Results In 2021, the global incidence of BSDs among children and adolescents reached 338 million cases, an increase of 49.32% compared to 1990 (EAPC = 0.86); Prevalence reached 14.23 million cases, an increase of 48.27% (EAPC = 0.85). During the same period, the DALYs rate decreased by 39.01% (EAPC = -1.9). Regionally, the burden was highest in sub-Saharan Africa, while the highest increase in incidence was observed in high-income North America. SDI-based stratification showed that DALYs were highest among infants in low SDI regions, while high SDI regions experienced a marked increase in incidence among adolescents aged 15–19 years. Gender analysis found that the incidence was higher among girls under five years of age, while the overall burden was higher among boys aged 15–19 years compared to girls. Neonates (0–6 days) were identified as the highest-risk group. Conclusion Although a moderate decline in DALYs rate was observed, the incidence and prevalence of BSDs continued to rise globally, with geographic, age-related, and genders disparities. These findings underscore the necessity of developing stratified and targeted intervention strategies to mitigate the increasing burden of BSDs among children and adolescents.